2023
DOI: 10.1007/s00396-023-05120-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbons’ structure and type on AC electrical properties of polymer composites: predicting the percolation threshold of permittivity through different models

Abstract: The AC electrical properties of EVA- and NBR-based composites filled with different conductive fillers were investigated. Result shows several magnitudes of increment in AC electrical conductivity and dielectric permittivity after the addition of these conductive fillers, indicating that these materials can be used as supercapacitors. The magnitude of increment was varied according to polymer and filler types. Herein, we also have tested the applicability of different sigmoidal models to find out the percolati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 65 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…A low metal content is sufficient for such ternary composite materials to exhibit a sufficient level of conductivity to be used as electrodes in electrochemical cells [ 72 , 73 , 74 ]. By replacing the metal itself with carbonaceous particles, including the use of pyrolyzed vegetable fibres [ 75 ], foams [ 76 ] or different carbon particles [ 77 , 78 , 79 , 80 ], it is possible to enable the design of materials at the level of performance required for their specific technological applications. In this sense, it is noticeable that the dispersion of zinc microparticles in increasing proportions in the EVA polymeric matrix increases the electrical conductivity of the composite, although it was observed that only the metallic microparticles in contact with the medium for all the proportions tested appear to suffer from chemical corrosion, since the electrical propagation processes for the material were not altered because the polymeric matrix acts as a protective barrier against the corrosion of the particles inside.…”
Section: Discussionmentioning
confidence: 99%
“…A low metal content is sufficient for such ternary composite materials to exhibit a sufficient level of conductivity to be used as electrodes in electrochemical cells [ 72 , 73 , 74 ]. By replacing the metal itself with carbonaceous particles, including the use of pyrolyzed vegetable fibres [ 75 ], foams [ 76 ] or different carbon particles [ 77 , 78 , 79 , 80 ], it is possible to enable the design of materials at the level of performance required for their specific technological applications. In this sense, it is noticeable that the dispersion of zinc microparticles in increasing proportions in the EVA polymeric matrix increases the electrical conductivity of the composite, although it was observed that only the metallic microparticles in contact with the medium for all the proportions tested appear to suffer from chemical corrosion, since the electrical propagation processes for the material were not altered because the polymeric matrix acts as a protective barrier against the corrosion of the particles inside.…”
Section: Discussionmentioning
confidence: 99%